Arterio–Ureteral Fistula as a Long-term Complication Following Retroperitoneal Presacral Ganglioneuroma Resection: Case Report in an Adolescent and Review of the Literature - Haecker, Theresa S.; Krebs, Thomas F.; Allmen, Regula von; Haecker, Frank-Martin (European Journal of Pediatric Surgery Reports, 2024)
Arterio–ureteral fistula (AUF) is a rare condition affecting nearby adult-only patients. Patients usually present with hematuria, often starting as intermittent hematuria which frequently increases, and may lead to hemorrhagic shock. Without rapid diagnosis and prompt treatment, AUF can be lethal. Risk factors for developing an AUF include a history of pelvic surgery mainly due to cancer, a history of pelvic radiation, a history of vascular surgery, or chronic indwelling ureteral stents (CIUS). Imaging to confirm diagnosis includes angiography, computed tomography (CT) scan, or retrograde pyelography, although AUF may be missed. Therefore, even if imaging is negative, the presence of hematuria of unexplained origin in combination with mentioned risk factors is highly suspicious for AUF and must be excluded.We report the case of a 16-year-old male patient who presented with a new onset of intermittent hematuria to our emergency room. The patient's history included previous pelvic surgery for resection of ganglioneuroma 6 years ago with bilateral replacement of the iliac artery and postoperative acute kidney failure with reconstruction of both ureters and CIUS. After the initial uneventful postoperative follow-up over 5 years, another Double J (DJ) catheter had to be placed into the right ureter due to hydronephrosis. Six weeks later, the patient presented with intermittent hematuria. Despite negative imaging, we performed immediate surgical exploration confirming the diagnosis of AUF. To the best of our knowledge, this is the first case of AUF under the age of 18 years reported in the literature.In conclusion, in patients with macrohematuria and a history of the abovementioned risk factors, AUF has to be kept in mind and must be reliably excluded.
Keywords: arterio–ureteral fistula; hematuria; chronic indwelling ureteral stent; pelvic surgery; adolescents